2014
DOI: 10.1097/jom.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Police Beyond Self-Report

Abstract: Police work is primarily a sedentary occupation, and officers tend to be more active on their off-duty days than during their work hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 16 publications
4
76
0
2
Order By: Relevance
“…Poorer physical and psychological health places them at greater risk of lifestyle-related diseases, such as cardiovascular disease (CVD) and diabetes, and overall mortality 1–5. Years of police service is associated with CVD risk,6 greater body weight7 and physical inactivity 8…”
Section: Introductionmentioning
confidence: 99%
“…Poorer physical and psychological health places them at greater risk of lifestyle-related diseases, such as cardiovascular disease (CVD) and diabetes, and overall mortality 1–5. Years of police service is associated with CVD risk,6 greater body weight7 and physical inactivity 8…”
Section: Introductionmentioning
confidence: 99%
“…Specific to occupational categories, Ramey and colleagues (101) noted that police officers were more active during off-duty days than on-duty days. This observation confirms the primarily sedentary nature of police work (111), despite the occasional burst of physical activity (100).…”
Section: Physical Activitymentioning
confidence: 99%
“…Alternatively, among a group of firefighters or police, it may be much more productive to bring fitness training equipment onsite. Their workdays are characterized by long periods of highly sedentary job tasks interspersed with occasional periods of intense physical exertion (101,106). In this scenario, achievement of and adherence to high physical fitness standards, including cardiovascular fitness, strength, muscular endurance, flexibility, and other health-and skill-related fitness components, should be encouraged, brought as close to the workflow as possible, and perhaps even be an integral part of the job itself.…”
Section: Program Design Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress leads to poor health, generally through the combination of the physical/physiological consequences of stress and through the ways that individuals do (or do not) respond to such stress (Gershon, Lin, & Xianbin, 2002). For example, research has shown an association between officer stress and lower officer self-perceptions of personal fitness (Gerber, Kellmann, Elliot, Hartmann, Brand, Holsboer-Trachsler, & Pühse, 2013) and that officers are more physically active on their days off work (Ramey, Perkhounkova, Moon, Tseng, Wilson, Hein, Hood, & Franke, 2014). Law enforcement officers also demonstrate poor dietary decisions, such as a lack of vegetable consumption (Kuehl et al, 2014), and drink energy drinks and excessive amounts of caffeine to deal with having to perform shift work (Monaghan et al, 2014).…”
Section: Literature Review On Law Enforcement Officer Health Wellnesmentioning
confidence: 99%